A New Approach for the Solution of Three-Dimensional Magnetohydrodynamic Rotating Flow over a Shrinking Sheet. (8th November 2010) - Motsa, S. S.; Shateyi, S.
Abstract : The numerical solution of magnetohydrodynamic (MHD) and rotating flow over a porous shrinking sheet is obtained by the new approach known as spectral homotopy analysis method (SHAM). Using a similarity transformation, the governing equations for the momentum are reduced to a set of ordinary differential equations and are solved by the SHAM approach to determine velocity distributions and shear stress variations for different governing parameters. The SHAM results are analysed and validated against numerical results obtained using MATLAB's built-inbvp4c routine, and good agreement is observed.